Bi‐directional roles of bone morphogenetic proteins in cancer: Another molecular Jekyll and Hyde?. (20th June 2013) - Ehata, Shogo; Yokoyama, Yuichiro; Takahashi, Kei; Miyazono, Kohei
<x xml:space="preserve">Abstract</x> Bone morphogenetic proteins (BMPs) are multi‐functional cytokines, which belong to the transforming growth factor‐β (TGF‐β) family. In some cancer tissues, aberrant expression of various BMP signal components has been detected. Here, we describe the divergent roles of BMPs during the progression of cancer. BMPs exhibit various effects on both cancer cells and on tumor microenvironments. BMPs inhibit the proliferation of cancer cells, with some exceptions. BMPs also induce the differentiation of certain cancer stem cells, and attenuate their aggressiveness. In parallel, BMPs play a critical role in the regulation of tumor angiogenesis and the metastasis of cancer cells. Some mouse xenograft models have revealed that cancer metastases are prevented by the inhibition of BMP signaling. Together, these findings imply that BMPs function as both suppressors and promoters of tumors in a context dependent manner. The bi‐directional characteristics of BMPs in cancer are similar to those of TGF‐β, which was previously described as a molecular 'Jekyll and Hyde.'